2011
DOI: 10.1136/amiajnl-2010-000039
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing alert acceptance: a novel approach for predicting the success of clinical decision support

Abstract: We evaluated potential modulators of alert acceptance by assessing content and human factors issues, and quantified the impact of a number of specific factors which influence alert acceptance. This information may help improve clinical decision support systems design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 22 publications
0
91
2
1
Order By: Relevance
“…A "one fits all" DDI warning system may not meet the needs of all user groups: On the one hand, consultants are interested in a system providing high sensitivity, and on the other hand, prescribers are interested in patient-specific support including detailed advice. [9] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A "one fits all" DDI warning system may not meet the needs of all user groups: On the one hand, consultants are interested in a system providing high sensitivity, and on the other hand, prescribers are interested in patient-specific support including detailed advice. [9] …”
Section: Discussionmentioning
confidence: 99%
“…[8] In particular, systems with improved acceptance are characterized by both, providing high quality of knowledge and presenting the messages in a user-friendly manner, including detailed advice. [9] To prevent overriding, one recent study investigated electronic hard stop alerts implemented in a CPOE system. [10] Although this intervention had a high impact on prescribing, the hard stop alerts induced clinically significant treatment delays in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 Usability is influenced by the alert's interface display, which can be modified using human factors principles to improve safety. [18][19][20] Previously, we conducted an investigation to assess the use of alerts in outpatient care, which identified 44 factors that influence the human-computer interaction between providers and alerts, along with several weaknesses of alert designs. 20 For instance, providers suggested that the timing of creatinine clearance alerts be modified so they appear in response to specific medication orders, such as allopurinol and non-steroidal anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Although it can help physicians more significantly and has greater practitioner performance, it is essential for physicians to understand these results and also necessary for users to have the relevant knowledge and experiences. Meantime, there are some scholars who point out that the effectiveness of clinical diagnosis decision support systems depends greatly on the degree of acceptance by physicians [19]. Wright, Sittig, Ash, Bates, Feblowitz, Fraser and Middleton [20], [21] think it should be worth more concerns that the corresponding management and governance pay a great role in the application and development of technology of the clinical diagnosis decision support.…”
Section: Related Workmentioning
confidence: 99%